MiR-324-3p suppresses migration and invasion by targeting WNT2B in nasopharyngeal carcinoma. Issue 1 (December 2017) - Liu, Chao; Li, Guo; Yang, Nianting; Su, Zhongwu; Zhang, Shuiting; Deng, Tengbo; Ren, Shuling; Lu, Shanhong; Tian, Yongquan; Liu, Yong; Qiu, Yuanzheng
Abstract Background Nasopharyngeal carcinoma (NPC) is a malignant epithelial carcinoma of the head and neck with strong ability of invasion and metastasis. Our previous study indicated that miR-324-3p, as a tumor-suppressive factor, could regulate radioresistance of NPC cells by targetingWNT2B . The purpose of this study is to investigate the role of miR-324-3p on migration and invasion in NPC cells. Methods Quantitative real time PCR was applied to measure the expression level of miR-324-3p andWNT2B mRNA in both cells and tissues, and the expression level ofWNT2B protein was determined by western blotting. The capacity of migration and invasion were tested by using wound healing and transwell invasion assay. Results Ectopic expression of miR-324-3p or silencing its target geneWNT2B could dramatically suppress migration and invasion capacity of NPC cells. Meanwhile, the alterations of miR-324-3p in NPC cells could influence the expression level of the biomarkers of epithelial-mesenchymal transition (EMT), including E-cadherin and Vimentin. Moreover, the expression of miR-324-3p was obviously downregulated andWNT2B was significantly upregulated in NPC tissues. The expression levels of miR-324-3p andWNT2B were closely correlated with T stage, clinic stage and cervical lymph node metastasis of NPC (P < 0.05). Conclusion miR-324-3p could suppress the migration and invasion of NPC by targetingWNT2B and the miR-324-3p/WNT2B pathway possibly provide new potential therapeutic clues for NPC.